Black book 3

Algebra Level 4

Let f ( x ) f(x) be continuous function such that f ( 0 ) = 1 f(0)=1 and f ( x ) f ( x 7 ) = x 7 x R f(x)-f\left(\dfrac { x }{ 7 } \right)=\dfrac { x }{ 7 }~\forall ~ x \in R , then find f ( 42 ) f(42) .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mehul Chaturvedi
Mar 6, 2016

f ( 42 ) f ( 6 ) = 6 f ( 6 ) f ( 6 7 ) = 6 7 f ( 6 7 ) f ( 6 7 2 ) = 6 7 2 f(42)-f(6)=6\\ f(6)-f(\dfrac { 6 }{ 7 } )=\dfrac { 6 }{ 7 } \\ f(\dfrac { 6 }{ 7 } )-f(\dfrac { 6 }{ { 7 }^{ 2 } } )=\dfrac { 6 }{ { 7^{ 2 } } } \\ \vdots \\ \vdots

adding upto infinity

f ( 42 ) f ( 6 7 ) = 6 + 6 7 1 + 6 7 2 + 6 7 3 + 6 7 4 f ( 42 ) f ( 0 ) = 6 + 1 f ( 42 ) = 6 + 1 + 1 = 8 \Rightarrow f(42)-f(\dfrac { 6 }{ { 7 }^{ \infty } } )=6+\dfrac { 6 }{ { 7 }^{ 1 } } +\dfrac { 6 }{ { 7 }^{ 2 } } +\dfrac { 6 }{ { 7 }^{ 3 } } +\dfrac { 6 }{ { 7 }^{ 4 } } \dots \infty \\ \Rightarrow f(42)-f(0)=6+1\\ \Rightarrow f(42)=6+1+1=\boxed{\color{#D61F06}{8}}

For f ( x ) f ( x 7 ) = x 7 f(x) - f \left(\dfrac{x}{7} \right) = \dfrac{x}{7} , f ( x ) f(x) must be of the first degree and since f ( 0 ) = 1 f(0) = 1 , f ( x ) f(x) must be of the form f ( x ) = a x + 1 f(x) = ax + 1 . Then, we have:

f ( x ) f ( x 7 ) = x 7 a x + 1 a x 7 1 = x 7 a x ( 1 1 7 ) = x 7 a ( 6 7 ) = 1 7 a = 1 6 f ( x ) = x 6 + 1 f ( 42 ) = 42 6 + 1 = 8 \begin{aligned} f(x) - f \left(\frac{x}{7} \right) & = \frac{x}{7} \\ \Rightarrow ax+1 - \frac{ax}{7} - 1 & = \frac{x}{7} \\ ax \left(1-\frac{1}{7}\right) & = \frac{x}{7} \\ a\left(\frac{6}{7}\right) & = \frac{1}{7} \\ \Rightarrow a & = \frac{1}{6} \\ \Rightarrow f(x) & = \frac{x}{6} + 1 \\ f(42) & = \frac{42}{6} + 1 = \boxed{8} \end{aligned}

I solved it by converting it into an infinite GP sum. But your method is much better :-)

Pulkit Gupta - 5 years, 3 months ago

f(x)= x/6 + 1.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...